Using the Direct Method on the Speaking Skills for Eight Grade Students at Islamic Junior High School of Al-Munawaroh Jombang - 05-lisa Ardiana fatmawati; Tika Mardiyah (Naatiq: Journal of Arabic Education, 2025)
Speaking skills are one of the important skills in learning Arabic and are the main means of communication using Arabic. However, the difference in student backgrounds and lack of confidence made them feel embarrassed in speaking Arabic. For this reason, in the process of learning speaking skills, teachers use direct methods as their efforts. This study aims to describe the implementation of the direct method in improving students Arabic speaking skills. This study is using a qualitative study. Data were collected through observation, interview, and documentation. The data were analyzed by data reduction, data presentation, and conclusion/verification. The findings of this research are as follows: This research reveals that in using direct method in learning speaking skills, the teacher first prepares a lesson plan that includes the selection of materials, methods, media, strategies, and forms of evaluation. Evaluation is done through speaking skills assessment, oral test, and written exam. The challenges in applying this method include differences in educational backgrounds, limited vocabulary and self-confidence, and limited facilities. Teachers address these challenges through appropriate instructional strategies and improved learning support. Based on these findings, future research is recommended to examine the effectiveness of the direct method using quantitative or mixed method approaches, involve broader research settings, and explore its integration with other instructional strategies or learning media to further enhance student’s Arabic speaking skills